Arabic Lexicology: Systematics of Compiling an Arabic Dictionary and Its lexicologists - Iis Susiawati; Ahmad Royani; Ahmad Dardiri (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2021)
This article discusses the Arabic codification process, the systematic compilation of Arabic dictionaries and the stories of Arabic lexicologists and their works from time to time. This study uses a library approach, with data collection techniques through reviewing and searching for library materials from books, journals and other relevant sources. The data collected were analyzed by the text study method with the aim of describing the content in detail and aiming to find out the contribution of dictionaries to the development of lexicology, how the process of compiling dictionaries was carried out by lexicologists, and the characteristics of dictionaries from time to time with their advantages and disadvantages. The results are: 1) The dictionary as a reference book in finding the meaning of words is certainly very helpful in the development of lexicology. 2) Lexicologists in producing dictionaries have struggled so hard, tirelessly, traveling from one corner of the village to another to get and understand the meaning of a word. 3) The works of lexicologists with various systematics of compiling dictionaries have characteristics with their respective advantages and disadvantages which are a major contribution to the development of lexicology as part of linguistics, especially Arabic linguistics and literature.يناقش هذا المقال عملية تدوين اللغة العربية والتجميع المنهجي للقواميس العربية وقصص علماء المعاجم العربية وأعمالهم من وقت لآخر. تستخدم هذه الدراسة نهج المكتبة ، مع تقنيات جمع البيانات من خلال المراجعة والبحث عن مواد المكتبة من الكتب والمجلات والمصادر الأخرى ذات الصلة. تم تحليل البيانات التي تم جمعها باستخدام طريقة الدراسة النصية بهدف وصف المحتوى بالتفصيل بهدف معرفة مساهمة القواميس في تطوير المعجم ، وكيف تم تنفيذ عملية تجميع القواميس من قبل علماء المعاجم ، وخصائص المعجم. قواميس من وقت لآخر مع مزاياها وعيوبها. النتائج هي: 1) القاموس ككتاب مرجعي في العثور على معنى الكلمات بالتأكيد مفيد جدا في تطوير علم المعاجم. 2) لقد ناضل علماء المعجم في إنتاج القواميس بشدة ، بلا كلل ، وهم يسافرون من زاوية في القرية إلى أخرى للحصول على معنى الكلمة وفهمها. 3) إن أعمال علماء المعاجم مع مختلف نظم تجميع القواميس لها خصائص مع مزايا وعيوب كل منها والتي تعد مساهمة كبيرة في تطوير علم المعاجم كجزء من علم اللغة ، وخاصة اللسانيات والأدب العربي.